2012
DOI: 10.1002/term.1612
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulsed electromagnetic fields and dehydroepiandrosterone on viability and osteo-induction of human mesenchymal stem cells

Abstract: The hypothesis of this work was that human bone marrow-derived mesenchymal stem cells (MSCs) are regulated by pulsed electromagnetic fields (PEMFs) and by intracrine conversion of an adrenal prohormone to dihydrotestosterone. The effect of PEMF and dehydroepiandrosterone (DHEA) on viability and osteogenic differentiation of human MSCs and on the viability of osteoblastic SaOS-2 cells was evaluated. It was found that PEMF promoted the viability rate of both cell types, whereas DHEA decreased the viability rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…This assay, as described by the manufacturer, uses a fluorescent staining reagent that binds specifically to the hydroxyapatite portion of the biomineralized structures35. The intensity of the green fluorescence is proportional to the amount of hydroxyapatite in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…This assay, as described by the manufacturer, uses a fluorescent staining reagent that binds specifically to the hydroxyapatite portion of the biomineralized structures35. The intensity of the green fluorescence is proportional to the amount of hydroxyapatite in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Yusa et al (2011) reported that Zn +2 stimulated the viability of human bone marrow MSCs, enhanced the biomineralization of cells, as well as differentiation and resulted in a significant up-regulated bone marker gene expression of type I collagen, OCN, ALP and BSP. In addition to the positive effects of Zn +2 on osteogenic differentiation, studies have evaluated the EMF effect on osteogenic promotion and osteoporosis treatment [45]. The results obtained in the study of Kaya et al (2011) [46] and Manjhi et al (2013) [16] indicated that 50 Hz, 1.5 mT EMF and chronic (2 h/d × 8 wk) ELF-MF exposure (17.96 micro-Tesla, 50 Hz) to SCI rats for 6 months may be useful in the prevention and treatment of osteoporosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many studies used PEMFs as adjuvant element, together with osteoinductive medium. In this experimental settings, increase in alkaline phosphatase (ALP) production, collagen type I and Runt-related transcription factor 2 (RUNX2) expression, and release of growth factors of the TGFβ family, such as BMP-2, were reported [41, 42, 44, 45]. On the other hand, their influence on the mineralization phase of osteogenic differentiation was controversial.…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 99%